2021
DOI: 10.1007/s12646-020-00583-7
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Resilience and Performance: the Mediating Role of Workers’ Well-being

Abstract: Associations among resilience, employee well-being (i.e., work engagement and burnout), and performance were examined. Up to date, to the best of our knowledge, no studies were carried out exploring the relationship between all three constructs into the same model from an organizational perspective. Consequently, the principal aim of this study was to understand and provide evidence regarding the above-mentioned relationships. Data were collected from a sample of 249 working professionals. The findings showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
(85 reference statements)
0
4
2
Order By: Relevance
“…This means that the more health workers feel stress due to work will make their performance decrease even though they have received the welfare that has been felt by health workers and the change is not significant. So the results of this study are different from previous research conducted by Cantante-Rodrigues et al (2021) that confirmed from the results of their research that employee welfare is able to significantly mediate the effect of work stress on employee performance.…”
Section: The Effect Of Work Stress On the Performance Of Health Worke...contrasting
confidence: 98%
“…This means that the more health workers feel stress due to work will make their performance decrease even though they have received the welfare that has been felt by health workers and the change is not significant. So the results of this study are different from previous research conducted by Cantante-Rodrigues et al (2021) that confirmed from the results of their research that employee welfare is able to significantly mediate the effect of work stress on employee performance.…”
Section: The Effect Of Work Stress On the Performance Of Health Worke...contrasting
confidence: 98%
“…Resilience is a positive strength of each individual that contributes to optimal development in preventing stress, negative emotions, and behaviour [13]. Studies on burnout and performance during Covid 19 mediated by fortitude were carried out by [14] and [15], which suggests that steadfastness can improve team member performance even though employees experience fatigue at work. Based on these studies, the proposed hypothesis is as follows: H1: job burnout has a positive effect on police performance H2: job burnout has a negative effect on police resilience H3: resilience has a positive effect on police performance H4: Resilience mediates the influence between job burnout and police performance Based on theoretical studies and the results of previous studies, it can be presented a conceptual framework of thought in Figure 1 below.…”
Section: Job Burnout Resilience and Performancementioning
confidence: 99%
“…Before the COVID-19 pandemic, the employees' well-being had already captured the interest of many researchers (Cantante-Rodrigues et al, 2021). For instance, in Portugal, in 2018, The Portuguese Association of Health Psychology estimated that approximately 18% of the Portuguese workers experienced burnout -an indicator of poor well-being (Aon EMEA Health Survey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Before the COVID-19 pandemic, the employees’ well-being had already captured the interest of many researchers (Cantante-Rodrigues et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%